Analysis of Eight Types of Floating Wind Turbines at Constant Wind Speed - Mohamed Maktabi; Eugen Rusu (Inventions, 2025)
The objective of this paper is to carry out response analyses of eight floating wind turbines and compare them together; this is something that is not seen in previous research papers. From this perspective, this paper will compare the response offset regarding the motions of the six degrees of freedom of the respective floating wind turbines. The applied forces that these analyses consider come mainly from constant wind forces applied on the wind turbines’ blades, as well as forces from waves and currents. Different response offset values are considered and compared regarding the different constant wind speeds, as well as the different velocities of waves and currents. This paper also provides various innovative references related to floating wind turbine analyses and software. Validation and verification studies are left for future work due to the complexity of the data provided in this paper. However, some comparisons are made between the obtained analysis results and some external references. The mentioned external references unfortunately have floating wind turbines with different wind and wave environmental conditions, power capacities, and dimensional characteristics. The results of the constant wind dynamic analysis of the eight floating wind turbines studied in this paper have shown that the maximum surge, sway, and heave response offset corresponds to the DTU Spar 1 floating wind turbine. The maximum roll and yaw response offset corresponds to the INO-WINDMOOR floating wind turbine. The maximum pitch response offset corresponds to the WindFloat floating wind turbine. The aero-hydro-servo-elastic method was used in the Sima software to run the analyses. It is a time-domain dynamic analysis, and it uses meters [m] and degrees [°] to describe the response offsets of the different floating wind support structures studied in this paper.